2020
DOI: 10.3390/cells9102247
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Targeting of the Signaling Controls of PNPLA3 to Effectively Reduce Transcription, Expression, and Function in Pre-Clinical NAFLD/NASH Settings

Abstract: Non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH) are emerging worldwide epidemics, projected to become the leading cause of liver transplants. The strongest genetic risk factor for NAFLD/NASH susceptibility and progression is a single-nucleotide polymorphism (SNP) in the patatin-like phospholipase domain-containing 3 gene (PNPLA3), rs738409, encoding the missense mutation I148M. This aminoacidic substitution interferes with the normal remodeling of lipid droplets in hepatocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 29 publications
3
24
0
1
Order By: Relevance
“…In keeping with these findings, tissue expression of PNPLA3 is significantly enhanced in biopsies of patients carrying the p.I148M polymorphism, whereas the rare rs2294918 PNPLA3 (p.E434K) variant attenuates the impact of the p.I148M on steatosis and circulating liver enzymes in NAFLD patients, whereby down-modulating PNPLA3 expression on the LDs (up to 50%) [57,60]. In addition, Schwartz and collaborators demonstrated that momelotinib, a drug used in clinical trials to treat myelofibrosis, may represent an effective modulator of PNPLA3 expression, yielding >80% reduction in PNPLA3 mRNA levels and hampering intracellular lipid content in human primary hepatocytes and stellate cells [60]. Another possible mechanism underlying the TG engulfment in hepatocytes carrying the p.I148M variant is linked to the impairment of lipophagy in hepatocytes, thus dampening autophagic fluxes and LD degradation [61].…”
Section: Pnpla3: Gambling On the Winning Horsesupporting
confidence: 58%
See 1 more Smart Citation
“…In keeping with these findings, tissue expression of PNPLA3 is significantly enhanced in biopsies of patients carrying the p.I148M polymorphism, whereas the rare rs2294918 PNPLA3 (p.E434K) variant attenuates the impact of the p.I148M on steatosis and circulating liver enzymes in NAFLD patients, whereby down-modulating PNPLA3 expression on the LDs (up to 50%) [57,60]. In addition, Schwartz and collaborators demonstrated that momelotinib, a drug used in clinical trials to treat myelofibrosis, may represent an effective modulator of PNPLA3 expression, yielding >80% reduction in PNPLA3 mRNA levels and hampering intracellular lipid content in human primary hepatocytes and stellate cells [60]. Another possible mechanism underlying the TG engulfment in hepatocytes carrying the p.I148M variant is linked to the impairment of lipophagy in hepatocytes, thus dampening autophagic fluxes and LD degradation [61].…”
Section: Pnpla3: Gambling On the Winning Horsesupporting
confidence: 58%
“…In addition, in mice overexpressing Pnpla3 p.I148M the softening of Pnpla3 expression by shRNA or by or proteolysis-targeting chimera (PROTAC)-mediated degradation reduced TG storages [59]. In keeping with these findings, tissue expression of PNPLA3 is significantly enhanced in biopsies of patients carrying the p.I148M polymorphism, whereas the rare rs2294918 PNPLA3 (p.E434K) variant attenuates the impact of the p.I148M on steatosis and circulating liver enzymes in NAFLD patients, whereby down-modulating PNPLA3 expression on the LDs (up to 50%) [57,60]. In addition, Schwartz and collaborators demonstrated that momelotinib, a drug used in clinical trials to treat myelofibrosis, may represent an effective modulator of PNPLA3 expression, yielding >80% reduction in PNPLA3 mRNA levels and hampering intracellular lipid content in human primary hepatocytes and stellate cells [60].…”
Section: Pnpla3: Gambling On the Winning Horsesupporting
confidence: 52%
“…Injection of antisense oligonucleotides against hepatic PNPLA3 in mice fed steatogenic and steatohepatitisinducing diets reduced fat, inflammation and fibrosis, with a more pronounced benefit in animals bearing the I148M protein variant [25]. The beneficial effect of PNPLA3 downregulation on J o u r n a l P r e -p r o o f hepatocellular fat and HSC transactivation could also be achieved by small molecules, such as momelonib, active on the JAK 1/2 and TGF-β/SMAD pathways [77]. Even if this compound could possibly suffer from off target effects and could not result suitable for chronic administration for a non-neoplastic condition, the aforementioned study provides a proof-of-principle that small molecules may achieve the goal of suppressing PNPLA3.…”
Section: A New Discovery Paradigm: From Human To Molecular Genetics Amentioning
confidence: 99%
“…Considering that the leading causes of mortality include cardiovascular events and cancer [18], NAFLD patients should be comprehensively classified based also on their prominent extrahepatic features rather than on their "intra-hepatic" manifestations alone [23][24][25]. Table 2 [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] summarizes some selected topics of future research. In conclusion, in 1997, the distinguished liver immunologist Albert J Czaja wrote that "NASH is currently a generic diagnosis that encompasses multiple diseases.…”
Section: Commentary and Research Agendamentioning
confidence: 99%